Crack identification and calculation of singular stress in plates using wavelet analysis - Nguyen, Hoài Sơn; Lam, Phát Thuận (Journal of Technical Education Science, 2009)
Crack identification and computing singular stress field surrounding the top of the crack is an important problem in evaluating the techniques. Various techniques have been studied and used to solve the problem above. In linear elastic fracture mechanics assumptions, the Finite Element Method (FEM) using Barsoum singular element at the top of the crack and the Wavelet transform have proved to be very effective. In this article, the crack is evaluated through Stress Intensity Factor (SIF) determined by Displacement Correlation Technique (DCT) and the singular stress field is computed by extrapolation methods from the FEM analysis results. Wavelet transform is also used with continuous and discrete transformation and has good result.